EFFECTS OF mDMDHEU CONCENTRATION ON SELECTED TECHNOLOGICAL PROPERTIES OF Neolamarckia cadamba WOOD - Van Luong, Nguyen; Thi Phuong Hoa, Ta (Journal of Forestry Science and Technology, 2017)
Research on the effects of mDMDHEU concentration at 10, 20 and 30% on the finishing abilityby 4 types of paints: brown alkyd, PU, cerise Lasure classic and dark gray Lasure classic paints, and on the adhesive ability of Neolamarckia cadambawood to 2 types of glue: Epoxy and PVA in room conditions and after outdoor weathering in within 12 months. The results indicates that the chemical concetration has an impact on adhesion of coating, whereas wood specimens treated with 10% concentration of mDMDHEU has lower adhesion of coating than specimens treated with 20% and 30% concentration. The adhesion of coating of wood specimens treated by chemicals decreases slightly compared to that before natural weathering. The color changing of coating of untreated wood specimens is higher than specimens treated by chemicals with 4 types of coatings. The color difference of wood surfaced coating of wood specimens treated with 10% concentration chemicals is considerably higher than specimens treated with 20 and 30% concentration chemicals.The color differences of wood surfaced finishing in treated samples with 20% and 30% concentration are trivial. Neolamarckia cadamba specimens treated with mDMDHEU have PVA and Epoxy bonding strength higher than untreated ones. PVA and Epoxy bonding strength increase of treated specimens, compared to control specimens after outdoor weathering within 12 months, is higher than that of treated specimens after keeping at room condition within 12 months or after gluing.